PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR (POC) KOTORAN KELELAWAR UNTUK BUDIDAYA ANGGUR LAUT DI DESA BOLOK, NUSA TENGGARA TIMUR - DImas Rizky Hariyadi; Zainal Usman; Riris Yuli Valentine; Sartika Tangguda (Jurnal Abdi Insani, 2023)
Fertilizer is a source of nutrients needed by plants, as well as sea grapes. Bat Manure found in the caves of Bolok Village have not been properly utilized and have the potential to be used as a basic ingredient in fertilizer. However, the bat manure must be processed first through composting because plants cannot absorb nutrients from organic matter that is still raw, regardless of its form and origin. The purpose of this community service activity is to provide community knowledge and skills regarding the manufacture of Bat Manure Liquid Organic Fertilizer starting from the preparation of materials, packaging to labeling. The method used in this service activity is a combination of lectures, discussions and practices. Community service activities were responded very well by the local community, this was shown by the active participation of the residents in all stages of the training so that they could run smoothly. It is hoped that in the future this fertilizer can become an alternative product so that it can overcome fertilizer scarcity and reduce production costs and can become an additional livelihood for the people of Bolok Village.